A Literature Review: Does Transformational Leadership impact and Effective in the Public Bureaucratic - Otto Berman Sihite; Carter Bing Andika; Agustian Budi Prasetya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
There is comprehensive literature in the public sector on the management of organizational change. Recent studies, however, have shown that due to transformative leadership, the particular context of public organizations may have implications for the organizational change of management. This research explores the effect of transformative leadership in relation to creative actions in order to create a successful corporate culture. Approaches to institutional change and direct supervisors' transformative leadership contribute to the successful adoption of organizational change in public organizations, and to what degree the public organizations' bureaucratic framework allows the implementation of organizational change unique. The application of transformative leadership in a public corporation is analyzed using the leader's direct questions. The findings suggest that with both expected and evolving transition strategies, bureaucratic institutions can successfully adopt transformational leadership. The contribution of transformational leadership depends on the style of approach to change and the nature of the organization.